Exercise Self-efficacy Improvements During Cardiac Rehabilitation: IMPACT OF SOCIAL DISPARITIES. Issue 3 (14th May 2023) - Candelaria, Dion; Kirkness, Ann; Bruntsch, Christine; Gullick, Janice; Randall, Sue; Ladak, Laila Akbar; Gallagher, Robyn
Abstract : Confidence to exercise improves in cardiac rehabilitation (CR) programs, providing an important source of resilience to support sustained exercise efforts over time. Social disparities, including ethnic minority background and being single, are important factors to consider in developing intervention to improve exercise self-efficacy within current CR programs. Abstract : Purpose: The objective of this study was to determine exercise self-efficacy improvements during cardiac rehabilitation (CR) and identify predictors of exercise self-efficacy change in CR participants. Methods: Patients with coronary heart disease at four metropolitan CR sites completed the Exercise Self-efficacy Scale at entry and completion. A general linear model identified independent predictors of change in exercise self-efficacy. Results: The mean age of patients (n = 194) was 65.9 ± 10.5 yr, and 81% were males. The majority (80%) were married or partnered, 76% were White, and 24% were from an ethnic minority background. Patients received CR in-person (n = 91, 47%) or remote-delivered (n = 103, 54%). Exercise self-efficacy mean scores improved significantly from 25.2 ± 5.8 at CR entry to 26.2 ± 6.3 points at completion ( P = .025). The majority of patients (59%) improved their self-efficacy scores, 34% worsened, and 7% had no change. Predictors of reduced exercise self-efficacy change were being from an ethnic minority (B =−2.96), not having a spouse/partner (B =−2.42), attending in-person CR (B =1.75), and having higher exercise self-efficacy at entry (B =−0.37) (adjusted R 2 = 0.247). Conclusions: Confidence for self-directed exercise improves in most, but not all, patients during CR. Those at risk for poor improvement (ethnic minorities, single patients) may need extra or tailored support, and screening for exercise self-efficacy at CR entry and completion is recommended. Differences identified from CR delivery mode need exploration using robust methods to account for complex factors.